Attitudes of Canadian medical students towards surgical training and perceived barriers to surgical careers: A multicentre survey - McLennan, Steffane; Purich, Kieran; Verhoeff, Kevin; Mador, Brett (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: Medical student interest in surgical specialties continues to decline. This study aims to characterize attitudes of Canadian medical students towards surgical training and perceived barriers to surgical careers.Methods: An anonymous survey was custom designed and distributed to medical students at the University of Alberta and University of Calgary. Survey questions characterized student interest in surgical specialties, barriers to pursuing surgery, and influence of surgical education opportunities on career interest.Results: Survey engagement was 26.7% in 2015 and 24.2% in 2021. General surgery had the highest rate of interest in both survey years (2015: 38.3%, 2021: 39.2%). The most frequently reported barrier was worry about the stress that surgical careers can put on personal relationships (2015: 70.9%, 2021: 73.8%, p = 0.50). Female respondents were significantly more likely to cite gender discrimination as a deterrent to surgical careers (F: 52.0%, M: 5.8%, p < 0.001).Conclusions: Despite substantial interest, perception of work-life imbalance was the primary reported barrier to surgical careers. Further, female medical students’ awareness of gender discrimination in surgery highlights the need for continued efforts to promote gender inclusivity within surgical disciplines to support early career women interested in surgery.